Quasi -Fully Cancellation Modules - M. A. Hadi, Inaam,; A.Elewi, Alaa (Iraqi Journal of Science, 2023)
Let M be an R-module. In this paper we introduce the concept of quasi-fully cancellation modules as a generalization of fully cancellation modules. We give the basic properties, several characterizations about this concept. Also, the direct sum and the localization of quasi-fully cancellation modules are studied.